Marigold Supercritical Extract as Potential Co-adjuvant in Pancreatic Cancer: The Energetic Catastrophe Induced via BMP8B Ends Up With Autophagy-Induced Cell Death - Gómez de Cedrón, Marta; Mouhid, Lamia; García-Carrascosa, Elena; Fornari, Tiziana; Reglero, Guillermo; Ramírez de Molina, Ana (Frontiers in Bioengineering and Biotechnology, 2020)
The recent development of powerful “omics” technologies (genomics, transcriptomics, proteomics, metabolomics, and lipidomics) has opened new avenues in nutritional sciences towards Precision Nutrition, which is a genotype-directed nutrition taking into account the differential responses to nutritional interventions based on gene variation (nutrigenetics) and the effect of nutrients on gene expression (nutrigenomics). Current evidence demonstrates that one third of cancer deaths could be prevented by modifying key risk factors, being diet among the most important risk factors due to its association with obesity. Additional factors such as composition of gut microbiome, immune system and the nutritional status will impact on the final outcome. Nutrient components and bioactive compounds from natural sources can modulate cancer progression or even the risk of developing this disease by regulating gene expression and/or associated risk factors such as obesity and chronic inflammation. Within the most popular methods for production of natural extracts, the green technology of supercritical fluid extraction (SFE) is quite popular nowadays, with special use in the extraction of compounds with low polarity which are soluble in supercritical CO2. The success of nutritional interventions based on the use of nutraceuticals requires several steps: (i) in vitro and preclinical demonstration of their antitumoral effects, (ii) knowledge of their mechanism of action and molecular targets, which will allow to identify the specific subgroups of patients that will benefice, (iii) the study of genetic variants associated to the differential responses and (iv) innovative approaches of formulations to improve the in vivo bioavailability of the bioactive ingredients. Herein, we investigate the antitumoral properties and mechanism of action of a Supercritical CO2 Extract of Calendula officinalis, commonly known as Marigold (Marigold SFE) in the context of Pancreatic Cancer. Mechanistically, Marigold SFE induces the expression of BMP8B which leads to an energetic catastrophe ending up with autophagy induced cell death (AICD). As metabolic reprogramming is a well-recognized hallmark of cancer, the direct impact of Marigold-SFE on pancreatic cancer cell metabolism encourage further research of its potential as co-adjuvant in pancreatic cancer therapy. Finally, we discuss innovative formulation approaches to augment the clinical therapeutic potential of Marigold SFE in nutritional interventions